(untitled) (Journal of Partial Differential Equations, 2016)
In this paper, we prove the existence of at least three nontrivial solutions for some biharmonic elliptic equation involving an integral term. The nonlinear term exhibits an exponential growth at infinity. Our method consists of a combination between variational tools and iterative technique.